STIM1 calcium sensor is required for activation of the phagocyte oxidase during inflammation and host defense - Zhang, Hong; Clemens, Regina A.; Liu, Fengchun; Hu, Yongmei; Baba, Yoshihiro; Theodore, Pierre; Kurosaki, Tomohiro; Lowell, Clifford A. (Blood, 2014)
The stromal-interacting molecule 1 (STIM1) is a potent sensor of intracellular calcium, which in turn regulates entry of external calcium through plasma membrane channels to affect immune cell activation. Although the contribution of STIM1 to calcium signaling in lymphocytes has been well studied, the role of this protein in neutrophil-mediated inflammation and host defense is unknown. We report that STIM1-deficient murine neutrophils show loss of store-operated calcium entry (SOCE) in response to both soluble ligands that activate G-proteins as well as Fcγ-receptor or integrin ligation that activates tyrosine kinase signaling. This results in modest defects in phagocytosis and degranulation responses but a profound block in superoxide production by the phagocyte oxidase. We trace the primary intracellular target of calcium to be protein kinase C isoforms α and β (PKCα and PKCβ), which in turn phosphorylate subunits of the oxidase leading to superoxide production. In vivo the loss of SOCE in stim1−/− chimeric mice results in marked susceptibility to bacterial infections but also protection from tissue injury in hepatic ischemia/reperfusion injury. These results demonstrate the critical role of STIM1-mediated SOCE and define major protein targets of calcium signaling in neutrophil activation during inflammatory disease. •STIM1-mediated calcium entry is critical for neutrophil superoxide release via activation of calcium-sensitive PKCα and PKCβ.•STIM1 deficiency results in profound susceptibility to bacterial infection, but also protection in hepatic ischemia/reperfusion injury.